2010
DOI: 10.2520/myco.60.89
|View full text |Cite
|
Sign up to set email alerts
|

Study design for dietary intake of aflatoxins of the adult Malaysian population

Abstract: The dietary intake of afl atoxin was targeted at the adult Malaysian population aged to years using the Total Diet Studies (TDS) approach as recommended by the World Health Organization (WHO). Data from the Malaysian Food Consumption Survey in was reviewed and foods were selected based on bibliographical knowledge and on expertise of analysts specialized in the routine analysis of raw and processed products for afl atoxin. Taking into consideration variabilities in contaminants as a result of production and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…These samples were subsequently individually composited for analysis according to geographical regions for food categorised as regional food and individual brands for food categorised as national food. Details of this study's design can be found in Chin and Abdullah (2010).…”
Section: Preparation Of Food Samples As Ready For Consumptionmentioning
confidence: 99%
“…These samples were subsequently individually composited for analysis according to geographical regions for food categorised as regional food and individual brands for food categorised as national food. Details of this study's design can be found in Chin and Abdullah (2010).…”
Section: Preparation Of Food Samples As Ready For Consumptionmentioning
confidence: 99%
“…In future studies, sample from other areas should be included, and should also include spice samples in fresh or wet form, as well as spices in cooked food ready for consumption. A proper survey of spice intake should be carried out to get the actual amount of daily intake among consumers in Malaysia [49,50].…”
Section: Dietary Exposure and Moe For Afb1 Contamination In Spices Mamentioning
confidence: 99%